Intersections of Fandom in the Age of Interactive Media : eSports Fandom as a Predictor of Traditional Sport Fandom - Brown, Kenon A. and Billings, Andrew C. and Murphy, Breann and Puesan, Luis (Communication & Sport, 2018)
This study focuses on comparing the uses sought and gratifications obtained when consuming media related to eSports and traditional sports; in doing so, relevant areas of overlap and distinction are ascertained. In all, more than 1,300 American eSports participants were queried as to their interest in both eSports and traditional sports fan/followership. Results revealed that eSports participants sought out media for both eSports and traditional sports for similar motivations, specifically social sport, fanship, and Schwabism. However, it is the magnitude of the motives that truly set eSports fans apart, with participants showing far more dedication and desire to engage with eSport content than in any other realm of the traditional sporting arena.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMTY3NDc5NTE3NzI3Mjg2